Recent Trends in Indian Capital Market - Currency Futures - Akula, Ravi; Anuradha Reddy, M. (Indian Journal of Finance, 2009)
Innovation is the key driver for success. Innovative instruments are the determining factors of success. Success for any exchange is driven by the twin synergistic play of efficiency and liquidity. Liquidity in the market brings about efficiency, and efficiency, in turn, increases liquidity. Any market/product that is able to establish this synergy effectively could be the ideal launch pad, irrespective of its listing on a single exchange or on multiple exchanges. The trading in currency futures had started on 29th August, 2008. It is believed that there is huge potential for the business in currency futures. The estimated volumes of currency futures are very high compared to all other trading volumes. The stock exchanges are getting ready to launch these innovative derivative products. This article is a modest attempt to discuss various aspects of currency futures.